A Comparison of Hispanic Refugee Parents’ and Adolescents’ Accuracy in Judging Family Cultural Views (Alberta Journal of Educational Research, 2005)
The Canadian school system requires refugee adolescents to develop the language, cross-cultural interaction skills, and direct modes of expression necessary for academic success. As peers become the agents of socialization into the host culture, adolescents may not attend to parents’ differential levels of receptiveness to changes away from their cultural heritage. In this study 50 Hispanic refugee parent-adolescent dyads rated the acceptability of 24 cultural shifts from their own perspective and the perspective of the other family member. Adolescents were poorer judges of family cultural views than their parents, creating potential for family conflict when school-based changes occur at home.